Trinity and revelation: An appraisal of Veli‐Matti Kärkkäinen. Issue 4 (4th September 2020) - David, Bright Singh
Abstract: In Trinity and Revelation, Veli‐Matti Kärkkäinen surveys a broad theological landscape before constructing a theological edifice for grasping the mystery of God's revelation in Christ with its significance for religious pluralism. This reader applauds Kärkkäinen for providing an integrated theological proposal that considers significantly not only the rich Christian theological tradition but also current scientific knowledge while respecting local or contextual theologies. This work will definitely contribute towards a more inclusive, open‐minded, balanced, and dynamic theological enterprises in the field of constructive theology.